Preparation of Silica-Phenyl Modified Methacrylate Polymer as Column Particles for Separation of Paracetamol and Caffeine - Annisa Mutiara Fitri; Handajaya Rusli; Muhamad Bachri Amran (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Silica-based column particles have been widely developed, but their particle size remains very small and heterogeneous, typically less than 3 µm. This small and inconsistent size poses challenges for interacting with the mobile phase during the separation of specific components due to the instability of the column particles . To address this issue, a method was developed using a methacrylate-based polymer core coated with silica and phenyl groups. The goal was to test column particles with a polymer core as the base, expecting improved performance compared to silica cores, with a target particle size >3 µm. This study evaluated the new method for separating paracetamol and caffeine, achieving excellent separation results (Rs 3.86). The method was optimized using a mobile phase consisting of methanol and water (60:40), a flow rate of 1.0 mL/min, and a wavelength of 274 nm. A single injection resulted in peak 1 for paracetamol and peak 2 for caffeine. The success of this method is evidenced by the production of sphere, homogeneous, with an average size of 3.17 µm. This analytical method has been effectively applied to the separation of paracetamol and caffeine, demonstrating its suitability for continuous use in drug separation validation.